Analytical Characterization of Deteriorated Stone Surfaces from Jahangir Tomb, Lahore, Pakistan - Gulzar, S.; Chaudhry, M.N.; Burg, J.P.; Saeed, S.A. (Asian Journal of Chemistry, 2014)
The paper describes severe deterioration throughout the historic structures in the Jahangir Tomb in Lahore (Pakistan) and specifically its richly decorated facades. The visually identified and megascopically studied deteriorated stone surfaces were sampled from the historic structures and analyzed with advanced chemical techniques including XRF, SEM-EDS in addition to the basic data generated by conventional methods. The results showed the presence of mainly sulphate minerals (gypsum: CaSO4·2H4O, anhydrite: CaSO4 and thenardite: Na2SO4), calcium oxalate with a high content of clay particles mainly illite. In addition we found a considerable content in nitrate (NO3–) and chloride (Cl–). An extensive network of fissures was found on surfaces directly exposed to rainwater. Furthermore, massive colonization by lichen was also found to affect the exterior facades of carved stone by strongly adhering to the substrate: this is clearly observed in XRD and scanning electron microscopic examination. The presence of all these deterioration products and factors demonstrate the action of hybrid atmospheric conditions combined with the surrounding polluted environment.